Hypochlorous acid induces a redox-dependent growth of C2C12 myoblasts: Hypochlorous acid-dependent C2C12 growth - Veskoukis, Aristidis S.; Christodoulou, Christina; Skaperda, Zoi; Kouretas, Demetrios; Liadaki, Kalliopi (Cellular and Molecular Biology, 2024)
Hypochlorous acid (HOCl) is a reactive chlorine species generated by the enzyme myeloperoxidase present in phagocytes. HOCl plays a vital role in inflammation and has been linked to tissue regeneration through redox signalling, however, the relevant evidence is rather scarce. The present investigation aimed to study the effects of HOCl on the growth of C2C12 myoblasts and its association with alterations of cellular redox profile. C2C12 cells were incubated for 10 min, 1 h and 24 h with a wide range of HOCl concentrations (628 pM - 4 M). Cell survival was increased when cells were incubated with HOCl concentrations between 6.28 μM and 628 μM, which are encountered in biological systems. Intriguingly, after a 10 min-incubation with 3 mM of HOCl, the highest cell growth was observed through a redox-related mechanism, as indicated by the decrease of the levels of reactive oxygen species and the enhanced levels of reduced glutathione measured by flow cytometry. The in vitro model created herein simulates the in vivo inflammatory and regeneration response of muscle cells and can putatively give mechanistic answers about the contribution of HOCl to muscle regeneration.